Abdominal suspension during massive panniculectomy: A novel technique and review of the literature. (June 2016) - Graf, Alexander; Yang, Kai; Klement, Kristen; Kim, Nicholas; Matloub, Hani
Abstract: Panniculectomy performed in patients with morbid obesity before or after massive weight loss improves body contour, incidence of soft tissue infection and overall functional status. However, obtaining adequate surgical exposure remains one of the most critical and challenging aspects of the procedure. We present the case of a 75-year-old veteran who underwent successful panniculectomy using a novel technique of abdominal suspension that is easier, more effective and less costly than previously used alternatives.